The Ottoman Measures to Prevent Attacks on the Hejaz Railway, 1908-1911: The Ottoman Archives as a Source - Khalil Ahmed, Asmahan Mastafa Tawfik (Al-Jami'ah Research Centre, 2023)
This study discusses the “Hamidiyah Hijazi Railway”, established by the Ottoman Empire to support Islamic politics worldwide. The importance of this study lies in its discussion, which focuses on a fragment of the glorious period of Islamic history that provided extraordinary services for Hajj pilgrims at that time. The Hijaz railway line was one of the most significant achievements of the Ottoman Empire and proved their intensive efforts in handling this matter as a religious matter. This study relies primarily on the Ottoman documents from 1908-1911, deposited in the Presidency of the Republic of Turkey Directorate of State Archives in Istanbul. This article focuses on the steps taken by the Ottoman Empire in securing the Hijaz railway from attacks by Bedouin tribes and maintaining its religious reputation concerning the safe journey of Hajj pilgrims via the railway. The author argues that the measures the Ottoman Empire took were ineffective in preventing these attacks. The Ottoman Empire secured the railway line by entrusting it to the sheikhs of the local tribes and holding celebrations for the development of the line. With this celebration, the Ottoman Empire wanted to show the importance of developing the Hijaz railway to unite Muslims under their flag and strengthen the Ummah movement in the spirit of Islamic unity in the confrontation with Western countries. [Studi ini membahas “Jalur Kereta Api Hamidiyah Hijaz”, yang dibangun Kesultanan Turki Uthmani untuk mendukung perpolitikan Islam di dunia. Pentingnya studi ini terletak pada pembahasannya yang berfokus pada satu penggal periode kejayaan sejarah Islam, yang memberikan layanan luar biasa untuk para jamaah haji pada masa itu. Jalur kereta api Hijaz ini dipandang sebagai salah satu capaian Islam yang paling signifikan dan menjadi bukti adanya upaya intensif Kesultanan Uthmaniyah dalam menangani urusan keagamaan ini. keuntungan. Studi ini terutama mengandalkan dokumen resmi Pemerintah Turki dari tahun 1908-1911, yang disimpan di Direktorat Arsip Kepresidenan Turki di Istanbul. Tulisan ini mengambil fokus pada langkah-langkah yang diambil Kesultanan Uthmaniyah dalam mengamankan di jalur kereta api Hijaz dari serangan suku-suku Badui dan menjaga reputasi keagamaannya terkait dengan keselamatan perjalanan jamaah haji melalui jalur kereta api. Penulis berargumentasi bahwa langkah-langkah yang diambil oleh Kesultanan Uthmaniyah tidak efektif dalam mencegah serangan-serangan tersebut. Kesultanan Uthmaniyah mengamankan jalur kereta api dengan mempercayakannya kepada para syaikh dari suku-suku lokal dan menyelenggarakan perayaan-perayaan atas pembangunan jalur kereta. Dengan perayaan ini, Kesultanan Uthmaniyah ingin menunjukkan pentingnya pembangunan jalur kereta api Hijaz dalam menyatukan umat Islam di bawah benderanya dan memperkuat gerakan ummat di bawah semangat kesatuan Islam dalam menghadapi negara-negara Barat.]